Biophysical profile: An effective technique for predicting the foetal outcome - Kobra, Khodeza Tul; Begum, Arzumanth Ara; Shova, Nazneen; Begum, Rashida (Journal of Dhaka National Medical College & Hospital, 2015)
Background: Maternal perception of foetal movement is one of the first signs of foetal life and is regarded as a manifestation of foetal wellbeing. Ultrasound imaging has broadened the scope of foetal assessment. Objective : Evaluation of biophysical profile as an effective technique for the assessment of foetal condition and to improve foetal outcome by early detection of foetal hypoxia. Study design and setting: This descriptive study was carried out for a period of one year from July 2009 to June 2010 in the department of Obstetrics and Gynaecology in Dhaka National Medical College Hospital (DNMCH). Patients and methods : This study was carried out on all high risk pregnant patients including decreased foetal movements who were admitted from 34-42weeks during the study time. One hundred and sixty patients were selected and their BPP score was recorded and were followed till delivery. Those who went into spontaneous labour and who were induced monitored during labour and at any sign of foetal distress immediate caesarean section was performed. Apgar score of newborn was noted at one and five minutes and those having poor score were resuscitated and followed till one week after delivery. Apgar score was compared with biophysical score (BPS). Results : In this study we performed biophysical profile in160 patients. Among them 62 patients were primigravidae and 98 were multigravidae. Out of 160 patients 146 were at term and 14 were preterm. In this study 108 had a BPP score of 10/10, 42 patients had a score of 8/10, and 10 patients had a score of 6/10.Majority of patients with normal biophysical score of 8-10/10 had good APGAR score. The rate of caesarean section was 73.75%. Concerning foetal outcome, 85% of cases with good outcome, low APGAR score at five minutes (<7/10) in 15% of cases, meconium staining in 16.25% cases, birth asphyxia in 10% of cases. Conclusion : The foetal BPP is highly accurate and appears to be an effective technique for assessment of foetal condition. J. Dhaka National Med. Coll. Hos. 2015; 21 (01): 6-11